ASPEK KONSTRUKTIVIS DALAM SENGKETA WILAYAH KASHMIR ANTARA INDIA DAN PAKISTAN - Agung Yudhistira Nugroho (Universitas 17 Agustus 1945 Jakarta, 2017)
Kashmir region is a complex area. Kashmir territorial dispute is caused by the impact on the political interests of both countries and through a unilateral claim of India and Pakistan. Issue a struggle power between India and Pakistan which the two countries mutually detterence launched through testing their nuclear weapons increasingly sharpening conflict between the two countries. The case of a prolonged struggle for Kashmir region forced the United Nations to find a solution as a step to solve the problem in Kashmir. The UN Security Council sends to India and Pakistan by bringing a proposal that suggested the two countries demilitarize over Kashmir to ensure that the polls are offered not take sides with one country. However, the proposal was rejected by India. India considered that the Kashmir issue is a bilateral issue with Pakistan. Resolution will be undertaken by the UN is always doomed to failure. This will be appointed by the author to see the extent of the territorial dispute escalating conflict.